Le protectionnisme : croissance, limites, voies alternatives : colloque du GRECO-CNRS-EFIQ, 1983, Aix-en-Provence - Lassudrie-Duchêne, Bernard; Reiffers, Jean-Louis; Bourguinat, Henri (Paris : Economica, 1985)
Bibliotheek François Vercammen
Frans
Monografie
Keywords: protectionisme